The lamp of Umm Hashim : and other stories - Ḥaqqī, Yaḥyá (Modern Arabic writing., 2004)
"In the first story in this volume, the very short "Story in the Form of a Petition," Yahya Hakki demonstrates his ease with gentle humor, a form rare in Arabic writing. In the following two stories, "Mother of the Destitute" and "A Story from Prison," he describes with typical sympathy individuals who, less privileged than others, somehow manage to scrape through life's hardships. The latter story deals with the people of Upper Egypt, for whom the writer had a special understanding and affection. It is, however, for the title story (in fact, more of a novella) of this collection that the writer is best known. Recounting the difficulties faced by a young man who is sent to England to study medicine and who then returns to Egypt to pit his new ideals against tradition, "The Lamp of Umm Hashim" was the first of several works in Arabic to deal with the way in which an individual tries to come to terms with two divergent cultures."--Publisher's description